Connection Initiation Breastfeeding Early (IBE) and Giving Exclusive Breast Milk at Permata Madina General Hospital Panyabungan City - Parrinduri, Nikmah Choiriah; Wiwi Wardani Tanjung (International Journal of Public Health Excellence (IJPHE), 2022)
Breastfeeding from an early age has a positive impact on both mother and baby. According to the results of Fika and Syafiq's research, mothers who do IBE are 2 to 8 times more likely to exclusively breastfeed. The purpose of this study was to determine the relationship between IBE and breastfeeding Exclusively in the Neonatal Room, Permata Madina Hospital , Panyabungan. The type of research that used is analytical research by design studies case control . Population on study this is mother which have baby age 6 – 12 months in the Neonatal Room at Permata Madina Hospital in Panyabungan City. Sampling is done by purposive sampling with a sample of 51 mothers. Data analysis was performed using chi square . The results of this study indicate the implementation of IBE have relationship that significant with gift breast milk exclusive (p value= 0.04 ) , mothers who carry out IBE have a 4 times greater chance of giving exclusive breastfeeding.